MEMBANGUN KOMUNIKASI EFEKTIF UNTUK MENINGKATKAN KUALITAS DALAM PROSES BELAJAR MENGAJAR - Tutut Handayani (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2011)
There are some factors such as the learners, classroom, method, and teaching material that are needed to be considered in teaching and learning process. A teacher in a teaching and learning process or an instructor in a seminar needs to have serious attention on those factors to reach goals. There could be different method and communication ways for a lesson. Therefore, a teacher or an instructor needs to be smart in applying effective communication strategy to make the teaching and learning strategy optimal. A teacher or an instructor can apply an effective communication strategy in two ways. First, s/ he needs to apply the three - pattern of communication; one-way communication, two-way communication and multiple communication. Second, she needs to apply the The 5 Inevitable Laws of Effective Communication; respect, empathy, audible, clarity, humble, which is more famous with its acronyms REACH and it means to get or to gain something. Since the actual communication is basically the way to win others’ attention, love, interest, concern, sympathy, responsiveness, and positive answers.